1996
DOI: 10.3109/13625189609150665
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic inflammatory disease in intrauterine device users

Abstract: Pelvic inflammatory disease (PID) has been associated with the use of intrauterine devices (IUDs) ever since they were introduced. In several mostly retrospective studies the incidence of PID was suggested to be as high as three- to ninefold in IUD users compared to non-users. Later epidemiological prospective studies showed a considerably lower risk comparing different types of contraception. Compared to non-contraceptive users the relative risk ranged from 1.8 in patients with copper-containing IUDs to 3.3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Also, in our study, pelvic pain was the most common presenting symptom at first PID episode, which is usually reported to be the key symptom of for the provisional diagnosis of PID 4,5,11,24,[26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in our study, pelvic pain was the most common presenting symptom at first PID episode, which is usually reported to be the key symptom of for the provisional diagnosis of PID 4,5,11,24,[26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…One of the muchdebated issues is whether IUD use as such increases a woman's risk of PID, independently of other risk factors for developing the disease. Whereas many studies in the past suggested that IUD use was an independent risk factor for PID development, more recent studies have claimed that this is not the case, except at the time immediately (21 days) following IUD insertion 24 .…”
Section: Introductionmentioning
confidence: 98%
“…In a review of 28 clinical studies including 25,674 women of whom 42.5% were nulliparous, Struthers reported a PID rate of 1.49 PID/ 100 women-year [25]. The risk of PID was later estimated to be 1.8 fold more important for Cu-IUD users than for non-contraceptive users, with a maximum incidence in the first 20 days [4]. Because of this risk, the use of UID in nulliparous women is controversial, even if stable monogamous relationships seem to protect from PID.…”
Section: Contraceptionmentioning
confidence: 94%
“…A study done by Beerthuizen found that nulliparous women are not at higher risk of PID than multiparous women. 12 A longitudinal study conducted by Wright demonstrated no relationship between the parity and the development of PID. 13 In itself delivery is not a risk factor for PID but delivery in untrained hands is a risk factor.…”
Section: Discussionmentioning
confidence: 99%